Through their lens: A photovoice study exploring pregnant and postpartum women's experiences, coping strategies and barriers to heat adaptation in an urban township in South Africa. - Chersich, Matthew; Scorgie, Fiona (My University, 2026)
Rising global temperatures and heatwaves pose major health risks, particularly for pregnant women, infants and other vulnerable groups. Using Photovoice, we aimed to foreground how pregnant and postpartum women in an urban township in Tshwane, South Africa, experience and cope with heat stress. Fourteen women participated in two structured workshops held during the hot season (December 2023-January 2024). The first included reflective discussions on coping with heat and basic photography training. Over two weeks, participants captured over 300 images using disposable cameras or mobile phones. Selected images were reviewed and discussed in the second workshop. Thematic analysis of photographs and workshop transcripts identified three key themes: health impacts, coping strategies and structural challenges. Women preferred staying home on very hot days, where they had greater control over their environment. However, they struggled to soothe overheated infants, which they found distressing. They used simple cooling methods such as bathing or wet cloths but faced constraints including heat-trapping housing materials, inadequate ventilation, and limited access to water and electricity. These challenges led to a state of “un-coping”—where adaptation efforts are insufficient or counter-productive. Viewed through the women’s “lens”, these findings highlight the need for targeted adaptation strategies to improve climate resilience.
PUBLISHED
Keywords: Maternal and child health; photovoice; climate change; hot temperatures; South Africa; Creative Arts Practice; International Development; Smart & Sustainable Planet; CLIMATE CHANGE; Child/Maternal Health; Photovoice; South Africa